Storm cycle - Johansen, Iris (St. Martin's Press, 2009)
Rachel Kirby, a computer genius whose beloved twin sister is dying from a chronc illness, receives a mysterious email from archeologist John Tanek who sits trapped inside a collapsed Egyptian tomb with a functioning laptop thousands of miles away. It turns out the collapse was no accident. John has discovered something very valuable in that tomb, something that humankind has been searching for throughout history, something that Rachel could use as it may hold the key to her sister's cure--if they both can stay alive long enough to unravel the ancient mystery.